Determinantes sociales y su relación con el rendimiento académico en los estudiantes del quinto grado de secundaria de la institución educativa experimental UNAP 2022 - Vargas Freitas, Andrea Alicia (2025)
The present research focused on determining the relationship between social determinants and academic performance in students in the fifth grade of secondary education at the I.E Experimental UNAP, 2022. This research, after the pandemic, was authorized by the educational authority, with a total of 90 students from the aforementioned institution, the quantitative thesis was developed with a non experimental - correlational design, which had a greater presence of men in 48.9% and women in 51.1%, of the three sections that were found operating in the Educational Institution. In the first group of results on the first variable, which was the social determinants, four dimensions studied were written in the group of results: the profession of the head of the household, the mother's educational level, main sources of income and housing conditions; and with regard to the second variable, the academic performance that was extracted from the weighting of the students' grades (booklet), an academic performance of 96.6% was satisfactory achievement and 43.3% was basic achievement. And, finally, the relationship between both variables was determined, using the Pearson Chi Square statistical test, a result was obtained p value = 0.729, which after comparing with the significance level α = 0.05. It was deduced that the variables are independent, they have no statistical relationship according to the results obtained, consequently, the null hypothesis is accepted and the alternative hypothesis is rejected.